(3JShjI GdefGRYGJ HGdWQb GdOHdheGSjI (B: s (3OQGSI dESgGeGJ GdeedcI GdYQHjI GdSYhOjI ai gPG GdeLGd (B/ s - (3UGdM Hf Ydi Hf ESeGYjd HOjhi s; (3eMeO SGeM YeQh s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2009)
(3JJfGhd gPg GdQSGdI ehVhY (B"(3JShjI GdefGRYGJ HGdWQb GdOHdheGSjI OQGSI dESgGeGJ GdeedcI GdYQHjI GdSYhOjI ai gPG GdeLGd(B"(3MjK jdbi GdHGMK fXQg YGeIYdi GdefGRYGJ GdOhdjI hGdZjQ GdOhdjI hKhGHJ GdOHdheGSjI GdSYhOjI hjJfGhd JhVjMG ddhSGFd GdOHdheGSjI dMd GdefGRYGJ GdOhdjI hgi GdeaGhVGJ hGdeSGYi GdhOjI hGdOhdjI hGdJMbjb hGdJhajb GdOhdjjf Ke jYQV JShjI GdefGRYGJ GdJi cGfJ GdSYhOjI WQaG ajgG HGdWQb GdOHdheGSjI(B.(3hgPg GdefGRYGJ CKjQJ eY Ohd GdLhGQ hgi(B:(3LeghQjI Gdjef(B:(3hOhdI bWQ(B:(3hOhdI GdEeGQGJ GdYQHjI GdeJMOI s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi s
(3HHdjhLQGajG(B: (3UaMGJ(B250-259s
Keywords: (3GdhSGFd GdOHdheSjI dMd GdefGRYGJ GdOhdjIs; (3GdJMbjb hGdJhajb GdOhdjjfs; (3GdeSGYi GdMejOIs; (3GdeaGhVGJ GdeHGTQI s; (3eTcdI GdMOhO GdSYhOjI GdjefjIs; (3eTcdI GdMOhO GdSYhOjI GdbWQjI s; (3GdbVjI GdadSWjfjIs; (3eTcdI WGdHGf s; (3GdhSGWI GdOhdjIs; (3eTcdGJ GdbQf GdGaQjbjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs